The Different Drivers of Innovation Activities in European Countries: A Comparative Study of Czech, Slovak, and Hungarian Manufacturing Firms - Prokop, Viktor; Stejskal, Jan; Kuvikova, Helena (My University, 2017)
In the era of knowledge economy, innovations are gaining increasing importance and becoming crucial for firms (countries) to gain their competitive advantage. However, most of countries are not able to exploit the innovation potential and failing during innovation and supporting processes. In this study, we use own multiple linear regression models and data from Community Innovation Survey to compare three European countries – Czech Republic, Slovakia and Hungary, which declined in the international rankings of competitiveness and innovative activities in recent years. Results confirm our claim that there is a need to find proper drivers´ that will allow creation of synergies and spillover effects. We empirically prove, that proper targeting of innovation drivers significantly influences the growth of firms´ turnover from innovated products that may lead to increasing of firms´ (national) competitiveness.
Odlišné podněty inovačních aktivit v Evropských zemí: komparativní studie českých, slovenských a maďarských průmyslových firem
Keywords: innovations; cooperation; public funding; manufacturing; Czech; Slovak; Hungary; inovace; kooperace; veřejné financování; průmyslové firmy; ČR; SR; Maďarsko